Characterization of the Vaginal Microbiome in Women of Reproductive Age From 5 Regions in Brazil. Issue 8 (August 2020) - Marconi, Camila; El-Zein, Mariam; Ravel, Jacques; Ma, Bing; Lima, Moises D.; Carvalho, Newton Sergio; Alves, Rosane R F.; Parada, Cristina M G L.; Leite, Sandra H M.; Giraldo, Paulo C.; Gonçalves, Ana K.; Franco, Eduardo L.; et al.
Abstract : Background: Composition of the vaginal microbiome is strongly related to a woman's reproductive health and risk of sexually transmitted infections. Ethnoracial, behavioral, and environmental factors can influence microbiome. The Brazilian population is unique in terms of miscegenation of ethnic groups and behavioral characteristics across different regions. We aimed to characterize the vaginal microbiome of women from 5 geographical regions of Brazil. Methods: We sequenced V3–V4 regions of 16S rRNA gene in vaginal samples of 609 reproductive-aged women. We performed logistic regression analyses to estimate odds ratios (OR) and 95% confidence intervals (CI) for the association between sociodemographic and behavioral factors with Lactobacillus -depleted microbiome (community state type [CST] IV). Results: Vaginal samples were grouped into 5 CST: CST I ( L. crispatus predominant, 30.5%), CST II ( L. gasseri predominant, 4.4%), CST III ( Lactobacillus iners predominant, 36.5%), CST IV ( Lactobacillus -depleted, 27.4%), and CST V ( L. jensenii predominant, 1.2%). Several factors were independently associated with CST IV, such as smoking (OR, 1.80; 95% CI, 1.02–3.18), number of partners (OR, 2.11; 95% CI, 1.20–3.70), and vaginal douching (OR, 2.24; 95% CI, 1.34–3.74). A protective effect was observed for milk/dairy intake (OR, 0.47; 95% CI, 0.27–0.82) and sitz bathing (OR, 0.43; 95% CI, 0.19–0.98). Conclusions: Nearly two thirds of Brazilian women may be at an increased risk for adverse outcomes associated with a vaginal microbiota characterized by the depletion of Lactobacillus or dominance by L. iners, whose protective role has been widely questioned. Several factors related to sexual behavior and intimate hygiene were associated with CST IV. Abstract : Nearly two thirds of reproductive-aged Brazilian women have either a Lactobacillus -depleted or a Lactobacillus iners –dominated microbiota, and thus at increased risk for sexually transmitted infections. Ethnicity was not associated with microbiome.Supplemental digital content is available in the text.